2021
DOI: 10.1093/jisesa/ieab062
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Yellow and Blue Sticky Cards for Detection and Monitoring Parasitoid Wasps of the InvasiveHalyomorpha halys(Hemiptera: Pentatomidae)

Abstract: The invasive Halyomorpha halys (Stål) is a significant agricultural and urban nuisance pest in many parts of the world. In North America, biological control of H. halys by parasitoid wasps in the families Scelionidae and Eupelmidae has shown promise. An effective technique for detection and monitoring native and exotic parasitoids is the deployment of yellow sticky cards; however, yellow cards also attract nontarget arthropods, reducing efficiency and accuracy of parasitoid screening. This study sought to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…An adventive population of Tr. japonicus , a parasitoid of H. halys in its native range, has also been confirmed in several US states (Talamas et al 2015a, Holthouse et al 2021, Peterson et al 2021, Dyer et al 2022). Prevalence of parasitoid species emerging from stink bug eggs can be habitat specific.…”
mentioning
confidence: 73%
“…An adventive population of Tr. japonicus , a parasitoid of H. halys in its native range, has also been confirmed in several US states (Talamas et al 2015a, Holthouse et al 2021, Peterson et al 2021, Dyer et al 2022). Prevalence of parasitoid species emerging from stink bug eggs can be habitat specific.…”
mentioning
confidence: 73%
“…Aside from Orthoptera, which are herbivores (Joern 1979) commonly captured on these traps, we selected these taxa because they are important beneficial insects either providing biocontrol (Chalcidoidea, Ichneumonoidea, Syrphidae) or pollination services (Lepidoptera, Syrphidae) (Bonet 2009;Herrmann, Buchholz, and Theodorou 2023;Skevington et al 2019). Given that these taxa are very commonly captured and known to be sensitive to environmental conditions (Benthall et al 2022;Eckberg et al 2015;Holthouse, Spears, and Alston 2021;Toennisson, Klein, and Burrack 2019), they provided an additional, more sensitive test beyond that which would be provided by simply examining the core taxa monitored at the site. Indeed, capture rates of four of the five additional taxa revealed a statistical difference between card types: the new cards appeared to be more attractive to Chalcid wasps, hoverflies, and Orthoptera, but less attractive to Ichneumon wasps.…”
Section: Discussionmentioning
confidence: 99%
“…Green, orange, and yellow traps caught the higher numbers of natural enemies, whereas the blue, purple, and white had a lesser effect. Yellow sticky traps are known to trap high numbers of natural enemies of Diptera and Hymenoptera [ 75 ]. An evaluation of sticky traps for monitoring thrips in a cowpea crop, found that beneficial insects were caught 1.7 times more on yellow than on blue traps [ 20 ].…”
Section: Discussionmentioning
confidence: 99%